Ambivalence model of suicidality [ABS-model]: an orientation model for the treatment of suicidal individuals - Teismann, Tobias; Britton, Peter C.; Forkmann, Thomas (Frontiers in Psychiatry, 2024)
The existing models for understanding suicidal ideation and behavior do not provide satisfactory orientation for clinical-therapeutic work with suicidal clients. Based on the observation that ambivalence accompanies the entire suicidal process and building on the empirical knowledge about suicidal ambivalence, this article presents the ambivalence model of suicidality (ABS model), a new clinical working model that aims to provide a framework for risk assessment, case conceptualization and treatment planning in the treatment of suicidal individuals. The model divides the suicidal process into three phases (uncertainty phase, transition phase and action phase), describes the psychological state within the different phases, and identifies phase-specific therapeutic interventions. The ABS model is a descriptive model that can be used to structure and organize crisis intervention and psychotherapy with suicidal patients.